Permanent and Transitory Components of GNP and Stock Prices - Cochrane, J. H. (Quarterly Journal of Economics, 1994)
This paper uses two-variable autoregressions to characterize transitory com-ponents in GNP and stock prices. Shocks to GNP holding consumption constant are almost entirely transitory, and account for large fractions of the variance of GNP growth. If consumption does not change, consumers must think that any GNP change is transitory. The facts that the consumption/GNP ratio forecasts GNP growth and that consumption is nearly a random walk drive this result. An implication is that consumption provides a good estimate of the "trend " in GNP. Prices and dividends behave similarly shocks to prices holding dividends constant are almost entirely transitory. I.